Contemporary Islamic Jurisprudence Studies on Monogamy, Polygamy and Divorce - Muhammad Hidayat; M. Arief Fadhilah; Rizky Zaidan Ketaren (Jurnal Sahabat ISNU SU, 2025)
This study examines how Islamic law (fiqh) views marriage in the forms of monogamy and polygamy, as well as how the process and reasons for divorce are viewed from a contemporary fiqh perspective. In everyday life, marriages do not always run smoothly. Some couples choose to live with only one partner (monogamy), while others choose to live with more than one partner (polygamy), in accordance with religious rules. Furthermore, divorce is not uncommon for various reasons. This study aims to examine how contemporary Islamic scholars view and provide solutions to these problems. The approach used in this study is a literature review, compiling various opinions from classical fiqh books and the opinions of contemporary scholars. The results of this study indicate that contemporary fiqh attempts to provide a fairer and more balanced view, adapting to current social conditions. Modern scholars increasingly promote monogamy as the ideal form of marriage, while polygamy is only permitted if there is a compelling reason and is carried out fairly. Divorce is still recognized in Islam, but should be a last resort after all efforts to improve the relationship have been exhausted.